Supporting Optimal Infant, Young Child and Maternal Nutrition and Health in Jordan: FY2021 2nd Quarter Report January 1st - March 31st, 2021. - Feed the Future Jordan Nutrition Innovation Lab. (Tufts University. Tisch Library., 2023)
The following is the quarterly report of the Feed the Future Jordan Nutrition Innovation Lab for the fiscal year 2021, starting from January 1st, 2021 until March 31st, 2021.; Keywords: nutrition, maternal and infant young child nutrition, human and institutional capacity, stakeholder engagement.; Leader with Associate Cooperative Agreement No. AID-OAA-LA-10-00006 Under Feed the Future Innovation Lab for Nutrition, Tufts University, Friedman School of Nutrition Science and Policy Cooperative Agreement Associate Award No.: 72027820LA00003.